PENGEMBANGAN LITERATUR SEJARAH AMERIKA BERBASIS ECOPEDAGOGY DI JURUSAN PENDIDIKAN SEJARAH - Abd Haris Nasution; Flores Tanjung; Arfan Diansyah (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2021)
Environmental intelligence or ecopedagogy today is important to be internalized in students as part of the environment. History records that increasing environmental intelligence / ecopedagogy is one of the solutions that have been implemented by the Americans in dealing with various pandemics such as the Blackdeath plague (14-15 century), smallpox epidemic (15 century), Yellow Fever (18 century), Spanish Flu (century 20). When the world is hit by the Sars, Mers and Covid-19 Pandemic in the 21st century, ecopedagogy is an important solution in terms of prevention. This study purpose is producing an ecopedagogy-based American History literature that can be used as a guideline / solution for the prevention of the Covid-19 pandemic against the background of the past experiences of Americans in overcoming various kinds of pandemics. This study uses the Research and Development method of the Borg and Gall model which consists of 4 stages, namely Preliminary Study, Development, Field Testing, Dissemination and Product Socialization. The results of this study indicate that as a medium of literature this is in the Good category with a mean score of 4.14 from the results of the validity test. While the material content obtained a score of 4.14 from the validity test results and entered into the good category. The limitation of this research is until the stage of product dissemination and socialization. This research has a novelty value in the form of American Green History literature products.